Synthetic polymer-polymer composites - Bhattacharyya, D.; Fakirov, Stoyko (Hanser, 2012)
This book provides another approach for the replacement of glass- and other inorganic fibers as reinforcement for polymer composites. The materials utilized include synthetic, petroleum-based polymesr but prepared here they come in the form of fibers, micro- or nanofibrils. Although this approach does not have the advantages of natural fibers being biodegradable and thus environmentally harmless. At the same time, synthetic polymer-polymer composites seem to be much more acceptable from an environmental point of view than glass fiber reinforced composites because tof their organic in nature. In addition to their environmental advantages, as compared to the polymer composites with mineral reinforcement with high loading rates, they are distinguished by much better specific mechanical properties. This property allows to manufacture light-weight products and constructions, a fact of particular importance in transportation vehicles and aircrafts. An international team of researchers, working in this area, collected the state-of-the-art results and demonstrate the application of synthetic, but organic materials in the form of carbon fibers, carbon nanotubes, or fibers or micro- and nanofibrils as replacements for mineral reinforcements.
Keywords: Polymeric composites.; elektronické knihy; electronic books